Variação no conteúdo protéico e pigmentar em variantes cromáticas de Gracilaria domingensis nas populações naturais de Rio do Fogo-RN, BRASIL - Pereira, Dinaelza Castelo (2009)
The seaweed Gracilaria domingensis is a common species in the coast of Rio Grande do Norte. This species lives in the intertidal zone, where colour strains (red, green and brown) co-occur during the whole year. Seaweeds that live in this region are exposed to daily changes and to the rhythm of the tide. During the low tide they are exposed to dissection, hiper-or hipo-osmotic shock, high temperatures and high irradiance. The aim of this study was to analyze whether the pigment and protein content of the colour strains of G. domingensis is affected by some environmental parameters in a temporal scale. The seaweeds were collected during 10 months in the seashore of Rio do Fogo (RN). The total soluble proteins and the phycobiliprotein were extracted in phosphate buffer and the carotenoids were analyzed by a standardized method through HPLC-UV. The pigments analysis showed that phycoerithrin is the most abundant pigment in the three strains. This pigment was strongly correlated with nitrogen and the photosynthetically active radiation. Chlorophyll presented higher concentrations than carotenoids during the whole, but the ratio carotenoid/chlorophyll-a was modified by incident radiation. The most abundant carotenoid was ß-carotene and zeaxanthin, which had higher concentrations in the higher radiation months. The concentration increase of zeaxanthin in this period indicated a photoprotective response of the seaweed. The three strains presented a pigment profile that indicates different radiation tolerance profile. Our results pointed that the green strain is better adapted to high irradiance levels than the red and brown strains